2005
DOI: 10.1111/j.1471-6402.2005.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Relational Boundaries among Heterosexuals, Gay Men, and Lesbians

Abstract: This study investigated the relative contributions of gender and sexual orientation as factors associated with the formation of boundaries in dyadic intimate relating in both same‐ and opposite‐sex couples. The study examined a relational pattern previously not empirically investigated but widely accepted as an actuality unique to lesbians; specifically, that lesbians tend to remain connected to ex‐serious‐relationship partners after breakup. The study utilized a research design approach emphasizing the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…To assess the mothers' evaluations of these relationships, we used one item of the Post Break-Up Connectedness-Behavior Questionnaire (PBC-B; Harkless & Fowers, 2005). This item elicits more qualitative information about the relationship between ex-partners: "My current relationship with my ex-partner is .…”
Section: Quality Of Mothers' Relationships With Ex-partnersmentioning
confidence: 99%
“…To assess the mothers' evaluations of these relationships, we used one item of the Post Break-Up Connectedness-Behavior Questionnaire (PBC-B; Harkless & Fowers, 2005). This item elicits more qualitative information about the relationship between ex-partners: "My current relationship with my ex-partner is .…”
Section: Quality Of Mothers' Relationships With Ex-partnersmentioning
confidence: 99%
“…In addition, lesbians and gay men may be especially likely to remain friends with former sexual partners (Solomon et al 2004, Weinstock 2004. In a recent study (Harkless & Fowers 2005), lesbians and gay men were more likely than were heterosexuals to agree, "When a relationship is ending, one of my biggest fears is that I will lose the friendship" or that it is important "to remain friends with someone with whom I've had a serious relationship." Lesbians and gay men were also more likely than were heterosexuals to report continued phone calls and social contacts with ex-partners.…”
Section: Relationship Formationmentioning
confidence: 99%
“…They found that gays and lesbians reported higher relationship satisfaction in their PDFs, and higher interpersonal contact with ex‐partner as a friend, compared with heterosexuals. Harkless and Flowers () investigated “postbreakup connectedness” (e.g., phone contact, social gatherings, desire to see, etc.) across sexual orientations.…”
Section: Postdissolution Friendshipsmentioning
confidence: 99%
“…With regard to sexual orientation, we predicted that (Hypothesis 2) lesbian, gay, bisexual, trans, and queer (LGBTQ) individuals will be more likely to have a PDF and have more of them currently and overall throughout life than heterosexuals because LGBTQ have a higher tendency of postdating connectedness (Harkless & Flowers, ) and have been shown to be more satisfied in their PDFs than heterosexuals (Lannutti & Cameron, ). Based on Harkless and Flowers's () finding, we also predicted that LGBTQ (Hypothesis 2a) individuals will be more likely to stay friends to maintain a sense of connectedness or security.…”
Section: Studymentioning
confidence: 99%